Estudo do processo de microfresamento em aço inoxidável ABNT 316L produzido por fundição e manufatura aditiva - Gomes, Milla Caroline (2022)
Micromilling is being used as a post-processing technique for materials manufactured by additive manufacturing (AM), since parts manufactured by this process have a low surface finish and dimensional accuracy. However, the machinability of materials manufactured by MA differs from materials manufactured by conventional processes. Therefore, it is important to investigate the cutting process of these materials. In order to contribute to this investigation, this work investigated the micromilling operation of ABNT 316L stainless steel samples produces by AM process called laser directed energy deposition (LDED), and conventional casting and solubilization process. In addition, four different deposition strategies were evaluated in the LDED process, namely: linear, zigzag, chessboard, and contour. To carry out the investigation, the wear of the microtools, the surface quality, the formed burrs, and the cutting force were analyzed. Also, a methodology for measuring the cutting force was developed using the Kistler 9265B dynamometer. It was investigated the influence of the feed per tooth on the surface quality, the formed burrs and the cutting force for the conventional sample and the one obtained by the contour strategy. The experimental tests consisted of manufacturing microchannels in each sample using a micromilling machine with a maximum spindle speed of 60,000 rpm and (Al,Ti)N coated carbide micromills with a cutting diameter of 400 µm. The results obtained showed that for the condition of higher cutting speed, the chessboard sample presented the higher wear. The roughness of the linear sample decreases for the higher cutting speed, however, for the other samples it was observed that the roughness increased with the cutting speed. The largest burrs were formed in the conventional sample and the smallest in the linear sample. It was also observed that the cutting force, the surface roughness, and the burr size are affected by feed per tooth, and their values increase with the increase of the feed per tooth for the contour and conventional samples. Therefore, it was possible to conclude that there is a difference in machinability between the materials manufactured by the different processes and strategies.